1997
DOI: 10.1007/s11661-997-0212-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface hardening of a ductile-cast iron roll using high-energy electron beams

Abstract: The effects of high-energy electron beam irradiation on surface hardening and microstructural modification in a ductile cast iron (DCI) roll are investigated in this study. The DCI roll samples were irradiated by using an electron accelerator (1.4 MeV), and then their microstructures and hardnesses were examined. Upon irradiation, the unirradiated microstructure containing graphites and the tempered bainite matrix was changed to martensite, ledeburite, and retained austenite, together with the complete or part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…14) Usually, T ad can be used to ascertain whether or not a synthesis for a given material can be accomplished by a combustion synthesis method. It has been empirically suggested that combustion will not become self-sustaining unless T ad Ն1 800 K. 15) The adiabatic temperature of Cu-Ti-Si system can be calculated using the following equation 16) according to reaction (10). Where DH (298) is the reaction enthalpy at 298 K, C P (P j ) and L(P j ) are the specific heat capacity and latent heat of products, P j , n j and x refer to the products, the mole fractions of Cu, respectively.…”
Section: Thermodynamic Considerationmentioning
confidence: 99%
“…14) Usually, T ad can be used to ascertain whether or not a synthesis for a given material can be accomplished by a combustion synthesis method. It has been empirically suggested that combustion will not become self-sustaining unless T ad Ն1 800 K. 15) The adiabatic temperature of Cu-Ti-Si system can be calculated using the following equation 16) according to reaction (10). Where DH (298) is the reaction enthalpy at 298 K, C P (P j ) and L(P j ) are the specific heat capacity and latent heat of products, P j , n j and x refer to the products, the mole fractions of Cu, respectively.…”
Section: Thermodynamic Considerationmentioning
confidence: 99%
“…Firstly, it can combine the advantages of the SHS reaction (such as low energy consumption, high time efficiency, and high product purity) 11–15 with the convenience of the casting process (such as easiness and high efficiency); on the other hand, it also can overcome the high porosity of SHS reaction products and the poor castability of the metal melt caused by the introduction of a high volume fraction of reinforcement. Secondly, the local region of casting rather than the entire casting is reinforced by the relatively costly particulates to achieve high wear resistance, while a good interface bond exists between the local reinforcing region and matrix to retain the high toughness and strength of the bulk of casting 9,16–18 . Therefore, compared with the monolithic composites, the locally reinforced composites are one promising type of materials due to the reduction of processing cost and the improvement of poor castability.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Unfortunately, most of the particulate reinforced MMCs in the previous studies are monolithic composites, while less work has been carried out on the locally reinforced MMCs. 4,[6][7][8] However, from the point of view of the application, the service life of components usually relies on their local wear resistance and it is desirable that local regions of the casting are reinforced by particulates to offer high-wear resistance while they retain high toughness and strength in the bulk casting. [6][7][8][9] Moreover, the high-volume fraction of reinforcement distributed only in the local region, which is difficult to or even cannot be realized in the monolithic composite fabricated by conventional casting route due to the poor castability, indicates that the locally reinforced composite is a promising type of material for the reason that it offers a virtually unique combination of low cost and high-wear resistance.…”
Section: Introductionmentioning
confidence: 99%